Water crisis in São Paulo: news coverage, public perception and the right to information - Martirani,Laura Alves (2016)
Abstract Based on materials published by different media outlets on the coverage of water crisis which affected the region of São Paulo in 2014 and on the concept of publizistikwissenschaft, this article seeks to evaluate the process of information construction in the public sphere. It appears that major media outlets embraced 'news' frameworks, while smaller and independent media adopted 'interpretative' frameworks. The former emphasized the problem of climate change and issues related to water consumption, while the latter stressed the lack of transparency of the state government and the sanitation company in managing the crisis and, together with social movements, they brought proposals and made demands. We conclude that although there was a process of extensive media coverage and public awareness of the problem of water supply, some aspects were silenced and that this process remained inadequate in terms of accounting for the structural causes involving security and the governance of water.